2011
DOI: 10.1097/ta.0b013e3181e97761
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite-Coated Pins Versus Titanium Alloy Pins in External Fixation at the Wrist: A Controlled Cohort Study

Abstract: In external fixation of the wrist, the use of HA-coated pins yields no clinical advantages: there is a trend toward a superior pin-bone anchorage, but a tendency of increased susceptibility for minor pin-track infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Pieske et al [25] , 2011 Pieske et al [26] , 2010 Placzek et al [16] Prospective nonrandomised comparative study . loosening (extraction torque < 150 Nmm per degree).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Pieske et al [25] , 2011 Pieske et al [26] , 2010 Placzek et al [16] Prospective nonrandomised comparative study . loosening (extraction torque < 150 Nmm per degree).…”
Section: Resultsmentioning
confidence: 99%
“…Five of the studies in this review found that HA-coating of pins improves bone fixation and therefore reduces loosening in patients undergoing external fixation. However, the results of the studies of Pieske et al [25,26] found that although there was a trend towards a superior clinical outcome, the results showed no significant superiority of HA-coated pins against uncoated pins and that the majority of clinical pin-site parameters were comparable in both groups. At the end of the fixator therapy, Pieske et al [26] , found there were a total of 9 loose pins out of 76 in the steel group (11.8%) compared to 6 loose pins out of 76 in the HA-coated group (7.9%), whilst Pieske et al [25] , showed there were 10 loose pins in the titanium group (12.5%) compared to 6 loose pins in the HAcoated group (7.9%).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This material produces a reduced susceptibility to bacterial adhesion. In a study by Pieske et al [24], titanium alloy pins were compared with stainless pins in 80 patients. There was no difference in the incidence of pin-tract infection.…”
Section: Discussionmentioning
confidence: 99%